Um olhar sobre o outro : estimulando a empatia por meio de contos no ensino de história - Seixas, Katia Patrícia Santos (2020)
A survey entitled ―A Look at the Other: Stimulating Empathy through Content in Teaching History‖ reflects on the use of short stories as a resource to stimulate empathy and historical analysis. It was carried out with students from the second and third years of high school, from Colégio Estadual Ivo do Prado, located in the neighborhood of Dezoito do Forte, in Aracaju / SE, between the months of October and November 2019. For this endeavor, the following texts were selected: ―Me, A Correct Man‖ (1977), by Murilo Antônio de Carvalho; ―Fear‖ (1944), by Anne Frank and ―Because Today is Saturday‖ (2016), by Maria José Silveira. From the work with these texts, a pedagogical notebook was created through which is described the methodology and how the options selected stimulate empathy and historical analysis. It also contains the contents that can be explored within the texts, activities used and the results of their application, as well as examples of texts written by the students. The perspective is that the material produced helps to socialize the results of the studies carried out and offer subsidies for reflections on the pedagogical practices experienced in the school routine that aims the growth of the student / citizen, prepared to live in society, respecting himself and his neighbors. The methodological procedures used were the survey of bibliographic material, and the constitution and analysis of the corpus. We sought to provide theoretical support from authors who developed studies on literature and short stories, such as Candido (2000), Lajolo (1991), Ferreira (2006), Gotlib (2006), Linhares (1993), Cortázar (1974), Magalhães (1973) , Bosi (1995) and Lima Sobrinho (1960). To address concepts of empathy and historical empathy, we seek support in Krznaric (2015), Hunt (2009) and Falcão (1989). In regard to learning, specifically historical learning, published in authors such as Fonseca (2003), Rüsen (1997), Barca (2006), Cerri (2011), Vigotsky (2005), Moreira (2011), Perrenoud (2008), Abud ( 2003), Bittencourt (2018), Pesavento (2005), Burke (2008), Alarcão (2011) and Zabala (1998), among others were taken in consideration. The corpus for analysis was built from the application of didactic sequences. When evaluating the results of the proposed activities, we were able to examine our own pedagogical practice, and, therefore, keep carrying out the action research-method, since, in this case, we had the researcher and the participants involved in a cooperative and participatory way.